Progress in Study of Low-Intensity Pulsed Ultrasound Acting on Inflammation-Related Signaling Pathways in Knee Osteoarthritis - OUYANG Hui; LIN Xingjin; WANG Jinying; SHEN Longbin; WANG Chengdong (康复学报)
Knee osteoarthritis (KOA) is a degenerative total joint disease involving pathological changes in the cartilage, synovium, subchondral bone, and periarticular ligaments and muscles of the joint. The onset of KOA is associate with the metabolic imbalance of articular cartilage and the activation of cytokines, especially the high expression of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α). They appear in multiple pathogenic signaling pathways of KOA, regulate the intracellular activity of KOA and play an important role in pathological processes such as chondrocyte destruction, extracellular matrix reduction, abnormal cartilage remodeling, subchondral ossification, and synovial inflammation. Low-intensity pulsed ultrasound (LIPUS), as a non-invasive and safe physiotherapy therapy, is essentially a low intensity mechanical energy, which can produce a series of physicochemical effects on cells through physical stimulation such as cavitation effect. LIPUS is effective in the treating KOA, achieving anti-inflammatory and analgesic effects and promoting cartilage repair by modulating the activity of inflammation-related signaling pathways such as IL-1β and TNF-α. The therapeutic mechanisms reviewed as following: 1) LIPUS can reduce the inflammatory response by enhancing the autophagic pathway of macrophages in the synovial membrane and inhibiting the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammatory vesicle pathway to reduce IL-1β production by macrophages; it can also acts through the classical wingless MMTV integration site family protein (Wnt)/β-linked protein signaling pathway on fibroblasts in the synovial membrane to inhibit synovial fibrosis. 2) LIPUS promotes chondrocyte production of extracellular matrix, regulates chondrocyte metabolism, and protects cartilage by inhibiting IL-1β -induced nuclear factor-activated B-cell κ light chain enhancer (NF-κB) signaling pathway and regulating mitogen-activated protein kinases (MAPKs) signaling pathway. 3) LIPUS protects cartilage by activating extracellular signal-regulated kinase 1/2 (ERK1/2) and phosphatidylinositol 3-kinase-protein kinase B (PI3K-Akt) signaling pathways to promote MSCs proliferation and differentiation, and also promotes transforming growth factor-beta1 (TGF-β1) production by MSCs through the integral protein-target of rapamycin (mTOR) signaling pathway to promote cartilage formation. The latest study also found that LIPUS promotes the migration and exosome release of MSCs for cartilage repair through the autophagic pathway, providing new ideas for the future direction of LIPUS combination therapy. This article provides a theoretical basis for clinical studies and combination treatment options for LIPUS by reviewing the research progress on the role of LIPUS in KOA inflammation-related signaling pathways.